Recent Advances for MOF‐Derived Carbon‐Supported Single‐Atom Catalysts. Issue 9 (27th February 2019) - Han, Aijuan; Wang, Bingqing; Kumar, Anuj; Qin, Yongji; Jin, Jing; Wang, Xinhe; Yang, Can; Dong, Bo; Jia, Yin; Liu, Junfeng; Sun, Xiaoming
Abstract: Single‐atom catalysts have drawn considerable attention because of their unique catalytic properties. However, the high surface energy of single atoms restricts their fabrication and creates significant challenges for further developments. In order to overcome this problem, metal organic framework (MOF)‐derived carbon materials can be served as ideal supports to anchor atomically dispersed metal atoms, due to their tunable particle size and shape features, by providing high surface area, porosity, thermal, and chemical stability. This review highlights the recent advances in i) different types of construction strategies for MOF‐derived carbon‐supported single‐atom catalysts, and ii) the catalytic applications of these MOF‐derived carbon‐supported single‐atom catalysts. Further, this review offers a valuable insight into the current challenges and future opportunities for MOF‐derived carbon‐supported single‐atom catalysts. Abstract : Metal organic framework (MOF)‐derived carbon materials are ideal supports to anchor atomically dispersed metal atoms. This review highlights the recent advances in the construction strategies and catalytic applications of the MOF‐derived carbon‐supported single‐atom catalysts. Further, this review offers a valuable insight into the current challenges and future opportunities in this rapidly ongoing area.